Characterization and analysis of migration patterns of dentospheres derived from periodontal tissue and the palate. (3rd October 2012) - Keeve, P. L.; Dittmar, T.; Gassmann, G.; Grimm, W. ‐D.; Niggemann, B.; Friedmann, A.
<x xml:space="preserve">Abstract</x> Background and Objective Stem cells derived from periodontal and palatal tissues may be useful for regenerative therapies of periodontal tissues. In addition to the use of single periodontium‐derived stem cells (pdSCs) and palatal‐derived stem cells (paldSCs), the application of pdSC and paldSC dentospheres, providing a pool of vital stem cells, may be a useful approach. As cell migration is a prerequisite for stem cells to regenerate a three‐dimensional tissue environment, we characterized pdSCs and paldSCs and investigated the migratory activity of dentospheres within a three‐dimensional environment. We also investigated the capacity of the dentospheres to grow on zirconium dioxide surfaces. Material and Methods The capacity of pdSCs and paldSCs to differentiate into the neuronal and osteogenic lineages was proved by RT‐PCR and immunohistochemistry through the detection of specific lineage markers, such as alkaline phosphatase, glutamate decarboxylase 1 (also known as GAD67, the 67‐kDa isoform of glutamate decarboxylase), neurofilament‐M and β‐III‐tubulin. The expression profile of surface molecules on pdSCs and paldSCs was analyzed by flow cytometry. Adhesion and growth of pdSC/paldSC dentospheres on zirconium dioxide surfaces were determined using confocal laser‐scanning microscopy. The migratory behavior of the cells was analyzed using a three‐dimensional collagen matrix migration assay. Results Both pdSCs and paldSCs were positive for epidermal growth factor receptor, CC chemokine receptor 2 and CXC chemokine receptor 4 expression and were able to grow on zirconium dioxide surfaces. Cell‐migration experiments revealed that both stem‐cell populations responded similarly to epidermal growth factor (EGF), monocyte chemotactic protein 1 (MCP‐1) and stromal cell‐derived factor 1alpha (SDF‐1α). Stimulation with EGF resulted in an increased migratory activity of both stem‐cell types, whereas the locomotory behavior of the cells was impaired by both MCP‐1 and SDF‐1α. Conclusion Dentospheres represent a pool of vital pdSCs/paldSCs. As a result of the migratory activity demonstrated, along with the capacity to grow on zirconium dioxide surfaces, dentospheres may be useful for regenerative purposes in periodontal tissues.